Decision-Making Attitudes in the Beef Chain Industry Innovation Adoption: Brazilian Case Studies - Carlos Rodrigues da Silva; Silvia Novaes Zilber; Priscila da Costa Rezende (International Journal of Supply Chain Management, 2021)
The research objective was to analyze the attitudes of decision-makers in the innovation adoption process in the Brazilian beef chain industry. The study’s approach was qualitative and exploratory, using multiple cases in the beef chain industry. To reach the objective, 17 rural properties in the Brazilian state of Mato Grosso do Sul were investigated. Unstructured interviews were conducted to map the decision-makers’ attitudes regarding the innovation adoption process. Content analysis was performed using the ATLAS.TI software. Findings: The attitudes of the decision makers to evaluate the internal environmental conditions showed the characteristics of informality, slowness, centralization, and conservatism. The factors that affect the innovation adoption were the cost-benefit ratio analysis, the cohesion and connection between what already exists in the organization and the innovative technology, and the uncertainties regarding the return on investment. Originality: The Brazilian Beef Chain has been suffering competition in the domestic and foreign market. Beef Chain can find in innovation a mechanism that allows it to improve its strategic position and thus remain competitive. The findings enabled the proposal of an innovation adoption model based on the attitudes of the decision-makers for the beef chain industry.